2021
DOI: 10.1186/s12877-021-02153-6
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving burnout of community-dwelling people with dementia in Hong Kong and New Zealand: a cross-sectional study

Abstract: Background Informal caregiving for people with dementia can negatively impact caregivers’ health. In Asia-Pacific regions, growing dementia incidence has made caregiver burnout a pressing public health issue. A cross-sectional study with a representative sample helps to understand how caregivers experience burnout throughout this region. We explored the prevalence and contributing factors of burnout of caregivers of community-dwelling older people with dementia in Hong Kong (HK), China, and New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 79 publications
4
30
0
Order By: Relevance
“…The impacts of providing care on psychological stress of informal caregivers is understood to be influenced by the caregiver’s background and contextual factors, as well as these primary and secondary impacts of the care situation ( Pearlin et al, 1990 ), with a misfit of demands and available resources associated with experiences of ‘burnout’ among informal caregivers ( Roth et al, 2015 ). In New Zealand, prior research with informal caregiver groups indicate significant deficits in formal support available in the provision of care roles under normal circumstances ( Jorgensen et al, 2010 ), with care for activities of daily living (ADLs), falls history and cohabitation with care recipient significant contributors to burnout among informal caregivers of people with dementia ( Chan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of providing care on psychological stress of informal caregivers is understood to be influenced by the caregiver’s background and contextual factors, as well as these primary and secondary impacts of the care situation ( Pearlin et al, 1990 ), with a misfit of demands and available resources associated with experiences of ‘burnout’ among informal caregivers ( Roth et al, 2015 ). In New Zealand, prior research with informal caregiver groups indicate significant deficits in formal support available in the provision of care roles under normal circumstances ( Jorgensen et al, 2010 ), with care for activities of daily living (ADLs), falls history and cohabitation with care recipient significant contributors to burnout among informal caregivers of people with dementia ( Chan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver burnout was associated with PWDs’ activities of daily living (ADLs) dependence and history of falls in the previous 90 days. Factors such as primary caregivers being adult children and the utilisation of allied health services were found to be protective to caregiver burn-out 13. As the social services and healthcare systems are different between Hong Kong and mainland China, factors contributing to caregiver burden may also differ between the two settings.…”
Section: Introductionmentioning
confidence: 97%
“…Factors such as primary caregivers being adult children and the utilisation of allied health services were found to be protective to caregiver burn-out. 13 As the social services and healthcare systems are different between Hong Kong and mainland China, factors contributing to caregiver burden may also differ between the two settings. Studies on caregiver burden of dementia caregivers conducted in northern cities of China showed that the average score of caregiver burden measured by the Zarit Burden Interview was 12.2±13.2, which lies in the mild range.…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts made advocating “aging in place”, Hong Kong has one of the highest institutionalization rates in the world, at 6.8%, with other countries ranging from 1.0% to 5.4% [ 12 ]. One of the possible reasons for this is the inability of families to shoulder the responsibility of such care [ 13 ]. Therefore, in order to support family members to provide care in the community, this study aims to increase our understanding of the caregivers’ experience along the end of life journey to strengthen interventions and further enhance policy formulation to support “aging well in place”.…”
Section: Introductionmentioning
confidence: 99%